Structural, optical, and magnetic behavior and the nucleation of a Griffiths-like phase in (Ca,V)-doped ZnO nanoparticles - Mrabet, S; Ihzaz, N; Bessadok, M N; Vázquez-Vázquez, C; Alshammari, M; Lemine, O M; Ananias, D; El Mir, L (Dalton transactions : an international journal of inorganic chemistry, 2025)
Single-phase (Ca,V) co-doped ZnO nanoparticles (Zn Ca V O, called hereinafter ZCVO) were synthesized a modified sol-gel method. The hexagonal wurtzite symmetry of the ZnO phase nanostructure, belonging to the 6 space group, has been confirmed through X-ray diffraction examinations using Rietveld refinement. No segregated secondary phases or Ca or/and V-rich clusters were detected. The TEM images clearly show the presence of nanoparticles exhibiting a diverse range of spherical shapes. The effect of co-doping on the optical band gap and crystalline quality was also investigated photoluminescence (PL), UV-vis, and Raman spectrometers. The - curve suggests a tenability of magnetic coupling which was discussed within the context of three competing magnetic phases using the 3D spin wave model and Curie-Weiss law. The lack of saturation of the - loop at 10 K suggests the presence of both paramagnetic (PM) and ferromagnetic (FM) phases in ZCVO NPs. The bound magnetic polaron (BMP) model provides a plausible explanation for the observed magnetic phase transition. Moreover, a Griffiths-like phase was observed for the first time, to our knowledge, in co-doped ZnO nanoparticles. This novelty may stem from the interplay between the antiferromagnetic (AFM) and FM interactions of the Ca and V ions, which are acquired by oxygen deficiency.